Blaze new trails and transform - Abd Razak, Dzulkifli (2009)
Datuk Dr Zainal Aznam Mohd Yusof, a member of the board of the National Economic Advisory Council, who was recently asked about it, said: "There are lots of things to be fixed. The roof is not leaking; we do not need a plumber. It is the foundation of the house. Probably, the whole house needs to be rebuilt. The transformation requires concerted efforts." In respect to building a "whole house" with a "rebuilt" foundation in transforming the economy, it seems that Malaysia is not alone.